Formulation and Assessment of Prednisolone Matrix Tablets with a Blend of Natural Polysaccharides: Colon-Specific Drug Delivery Via Wet Granulation Approach - Ratne, Nandini; Gavaroji, Shankar; Vohra, Samriti; Tripathi, Gireesh; Chandna, Amit; S. Uttekar, Pravin; Siddiqui, Zeba; Mohammed, Tasneem (Journal of Neonatal Surgery, 2025)
This study aimed to evaluate the formulation and characterization of matrix tablets using a natural polysaccharide blend of Angelica sinensis polysaccharide and Tamarind Seed Polysaccharide (AT-P). The blend was prepared in a 1:1 ratio and assessed for its potential as a binding agent in controlled-release tablet formulations. Preformulation studies, including pH, viscosity, bulk density, tapped density, and compressibility index, were conducted to ensure compatibility and stability. Five matrix tablet formulations (TF1 to TF5) were developed using wet granulation with Prednisolone as the active pharmaceutical ingredient. The tablets were subjected to various evaluation parameters such as thickness, hardness, friability, and content uniformity, followed by in vitro release studies in both the presence and absence of rat caecal matter to simulate colonic conditions. The kinetic modeling of drug release data revealed that TF3 followed zero-order kinetics, while TF2 and TF5 exhibited strong fits to both zero-order and Higuchi models. In the presence of rat caecal matter, a significant acceleration in drug release was observed, indicating the responsiveness of the formulations to the colonic environment. The study concluded that the natural polysaccharide blend (AT-P) is a promising excipient for controlled drug delivery systems targeting the colon.